Gender: A trademark with ideology - Fernández Méndez, Colin (2020)
The objective of the research is to deliver a deep analysis in the hands of the reader, which will surely generate debate, in reference to influence of the modern concept attributed to the term Gender has over a society that still recognizes the human being as a man or a woman, as a male or female being. Putting therefore in latent threat, its inescindible character. Extrapolating what happened with well-known brands, in which the products on the market, after experiencing a brand metonymy (brand vulgarization), become distinguished, from their original noun to their brand name, passing, at the beginning of having two identity denominations, on one. Becoming predominant for the collective subconscious, the name relative to its brand. In the same way, by the identity metonymy, in which the original identity of the human being, of man or woman, is replaced with a gender denomination, assigned by the ideologized gender (gender ideology), expanding these days around the world, and contained in a diverse list that according to some specialists would already exceed more than 100 genders registered and recognized by organisms and entities, which far from understanding the devastating effects that it would unfold on our own identity, and on our human sexuality, which is precisely what they give the person an unalterable and indivisible trait, they promote them classifying them according to an ambiguous social construction that the person infallibly feels they have forged, to be determined with an identity that fits a profile drawn up ideologically, and is exclusively linked to their sexual orientation.